Penggunaan Al-Qur’an Kisah The Fantastic Adventure Dalam Meningkatkan Motivasi Belajar Al-Qur’an Santri Pondok Pesantren Rahmatul Asri - Nurvadillah Nurvadillah; Muhammad Saleh; Muh. Dahlan; Usman Usman; Marhani Marhani; Khaerul Muawan (Departement of Mathematics Education, 2024)
This thesis discusses the use of Al-Qur'an The Fantastic Adventure in enhancing the learning motivation of Al-Qur'an among students at Rahmatul Asri Islamic Boarding School. This research aims to understand the concept of the storytelling approach in Rahmatul Asri Islamic Boarding School and examine the influence of using Al-Qur'an The Fantastic Adventure on students' learning motivation at Rahmatul Asri Islamic Boarding School. The study employed a pre-experimental method with a one-group pretest-posttest design, involving 34 female students from Grade VII of MTs Rahmatul Asri. Data were collected through a concept comprehension test and a learning motivation questionnaire administered before and after the treatment. The findings of the study showed a significant improvement in students' concept comprehension and learning motivation. The average Primary Motivation of the students increased from the